MODEL MANAJEMEN DATA PADA PENGELOLAAN ARSIP ELEKTRONIK: PENERAPAN DATA MANAGEMENT BODY OF KNOWLEDGE: Array - Parno Nusantara (Jurnal Kearsipan, 2018)
Data within the framework of managing digital records are very important. However, there are data that are considered non-qualified due to its invalidness, duplication and retrieval issue. It happens because there are no control over reliability and authenticity, and organization fail to implement electronic records activity. As a result of non-qualified data, the information could not be obtained within second in accurate form. This study aims to describe the needs of data management within the scope of electronic records management to produce qualified information. The data management model is being developed through an analysis within framework of DMBoK (Data Management Body of Knowledge) and equipped with archival key concept. The framework is used because of its wider scope and easily customized to the needs of the organization. The sources are obtained through literature studies and field observations at Preservation Unit of National Archives of Indonesia. The results are data management including data governance, reference and master data management and data quality management.